2014
DOI: 10.1136/gutjnl-2014-307650
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloritargets cancer-associated apical-junctional constituents in gastroids and gastric epithelial cells

Abstract: Objective Helicobacter pylori strains that express the oncoprotein CagA augment risk for gastric cancer. However, the precise mechanisms through which cag+ strains heighten cancer risk have not been fully delineated and model systems that recapitulate the gastric niche are critical for understanding pathogenesis. Gastroids are three-dimensional organ-like structures that provide unique opportunities to study host-H. pylori interactions in a preclinical model. We used gastroids to inform and direct in vitro stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 46 publications
4
118
0
1
Order By: Relevance
“…Gene manipulation studies have further highlighted a critical role of claudin-7 in maintaining the epithelial integrity in the mucosal epithelium as loss of claudin-7 results in inflammation and neonatal death [54,55]. Of interest, loss of claudin-7 expression was also recently associated with H. pylori-associated gastric cancer [56]. Thus, considering that the changes in claudin expression can modulate epithelial and immune homeostasis, the effect of the changes in claudin expression may be influenced by the tissue environment and context of the disease.…”
Section: Claudins and Cancer: Causal Correlationmentioning
confidence: 96%
“…Gene manipulation studies have further highlighted a critical role of claudin-7 in maintaining the epithelial integrity in the mucosal epithelium as loss of claudin-7 results in inflammation and neonatal death [54,55]. Of interest, loss of claudin-7 expression was also recently associated with H. pylori-associated gastric cancer [56]. Thus, considering that the changes in claudin expression can modulate epithelial and immune homeostasis, the effect of the changes in claudin expression may be influenced by the tissue environment and context of the disease.…”
Section: Claudins and Cancer: Causal Correlationmentioning
confidence: 96%
“…A separate study that found activation of NF-κB following injection of H pylori into mouse gastric epithelial organoids; 84 it reported upregulation of Sonic hedgehog, a protein involved in vertebrate development and the immune response to H pylori 84 . In a similar study, Wroblewski et al showed that H pylori infection of mouse gastric epithelial organoids resulted in mislocalization of occludin at the tight junction, previously observed in vivo 138, 139 . Similar to findings from PSC-derived gastric organoids, this study demonstrated that only H pylori variants that expressed CagA increased proliferation in gastric organoids 138 .…”
Section: Models Of Gi Diseasementioning
confidence: 68%
“…In a similar study, Wroblewski et al showed that H pylori infection of mouse gastric epithelial organoids resulted in mislocalization of occludin at the tight junction, previously observed in vivo 138, 139 . Similar to findings from PSC-derived gastric organoids, this study demonstrated that only H pylori variants that expressed CagA increased proliferation in gastric organoids 138 . Together, these studies have shown that H pylori infection can be modeled gastric organoids and can be used to study gastric transformation.…”
Section: Models Of Gi Diseasementioning
confidence: 68%
“…As reported, CagA translocation is rele vant to mislocalization of ZO1 in epithelial cells [47,48] . Studies revealed that H. pylori altered expression and localisation of claudin7, a cancerassociated tight junction protein, in gastroids and human epithelial cells, which was mediated by βcatenin and snail activation [49] . A recent study demonstrated that H. pylori diminished acidinduced tightening of cell junctions, affected the response of epithelial cells to acid, which took effects in inflammatory response and alteration of the barrier function [50] .…”
Section: H Pylori Disrupts Junctions and Polarity Of Epithelial Cellsmentioning
confidence: 99%